2020
DOI: 10.1186/s12872-020-01537-7
|View full text |Cite
|
Sign up to set email alerts
|

The minimal informative monitoring interval of N-terminal pro-B-type natriuretic peptide in patients with stable heart failure

Abstract: Background: N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a potential biomarker for monitoring the status of heart failure. However, the optimal monitoring interval of NT-proBNP is unknown. This study sought to investigate the minimal informative monitoring interval of NT-proBNP in patients with stable chronic heart failure. Methods: This retrospective cohort study included patients who were admitted due to heart failure and subsequently followed with serial NT-proBNP measurements in a tertiary hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Another concern in this study and in other studies on serial NT-proBNP measurement is the intra-individual variability and measurement error, which can account for up to 40% of its change in patients without HF and up to 60% in patients with stable HF per previous reports . This complicates the distinction of the true change from the noise and may be one reason why the continuous models demonstrated nonsignificant results after adjustment .…”
mentioning
confidence: 78%
“…Another concern in this study and in other studies on serial NT-proBNP measurement is the intra-individual variability and measurement error, which can account for up to 40% of its change in patients without HF and up to 60% in patients with stable HF per previous reports . This complicates the distinction of the true change from the noise and may be one reason why the continuous models demonstrated nonsignificant results after adjustment .…”
mentioning
confidence: 78%
“…Moreover, the magnitude of difference between the POC and laboratory devices is similar to those seen between the various laboratory assays for BNP and NT-proBNP produced by different manufacturers, 18 , 19 as immunoassays vary with respect to antibody specificity 20 and the population characteristics of those assessed. 21 Perhaps more important are the few recorded cases where there has been significant variation from visit to visit, and lack of concordance between POC and laboratory readings ( Figures 2 3 ), suggesting operator error rather than measurement bias. If POC testing is to be incorporated into routine primary care, it is imperative that operators are trained in its usage, and checks are developed to prevent and identify irregular results.…”
Section: Discussionmentioning
confidence: 98%
“…In cardiomyocytes with disorganized sarcomeres, all the texture quality parameters dramatically drop. The loss of a correct sarcomere structure is a typical feature of some heart failure pathologies (cardiac hypertrophy and cardiomyopathies) 36 38 . Moreover, sarcomere disruption is frequently correlated to changes of the expression of both contractile and regulatory proteins 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The loss of a correct sarcomere structure is a typical feature of some heart failure pathologies (cardiac hypertrophy and cardiomyopathies) 36 38 . Moreover, sarcomere disruption is frequently correlated to changes of the expression of both contractile and regulatory proteins 38 , 39 . We observed that the expression of sarcomeric α-actin and Tropomyosin proteins is altered and we propose that the skewed protein ratio of two (in our experimental conditions) proteins of those making up the sarcomeres may contribute to disrupt their organization, as also reported previously 14 , 31 , 40 .…”
Section: Discussionmentioning
confidence: 99%